A new species of Proceratophrys (Anura: Leptodactylidae) from the Amazon rain forest - Giaretta, Ariovaldo A.; Bernarde, Paulo S. [UNESP]; Kokubum, Marcelo N. de C. [UNESP] (JSTOR, 2000)
A new Proceratophrys from Rondonia, Brazil, is described based on adults and tadpoles. The new form represents a species with eyelids bordered by large, irregularly arranged, warts; postocular swellings absent; snout obtuse with flaring lip in profile; tympanum defined as a depression in the skin; and dorsal surfaces of body and leg bearing high elevated warts. The new species extends the known distribution of the genus to the northwest and represents the first described species of Proceratophrys from the Amazon rain forest. We discuss the species group arrangement in Proceratophrys based on morphology, geographic distribution, and habitat.
Keywords: Proceratophrys